Developing reading skills : advanced - Markstein, Linda; Hirasawa, Louise (Rowley, MA : Newbury House, 1983)
A collection of texts emphasizing guided reading practice and the development of reading speed, for those who want to strengthen their reading skills for academic, personal, or career purposes.
Keywords: English language -- Textbooks for foreign speakers; Readers; English language -- Textbooks for foreign speakers; Readers